The Effect Of CR, DER, And DAR On Profitability On Cigarettes Listed On The Indonesia Stock Exchange Period 2015-2017 - Ripki mohamad sopian; Ardi julianto; Pace Riansyah Sitohang (Westscience Press, 2023)
This study aims to determine the extent of the influence of the current ratio (CR), Debt to asset ratio (DAR), and Debt to equity ratio (DER) on profitability. This research was conducted on cigarette companies listed on the Indonesia Stock Exchange for 2015-2017. The sampling method used was the purposive sampling method with a total sample of 4 observations. The data used is secondary data in the form of audited financial reports registered and published by the Indonesia Stock Exchange through the website www.IDX.co.id. The analytical method used in this research is multiple linear regression analysis with the SPSS Statistics 24 tool. The descriptive statistical test is used to describe the data in the study; the classical assumption test is used to test the existence of bias estimates. The results of this study indicate that partially DAR and DER do not affect profitability while CR somewhat affects profitability. Simultaneous effects, namely CR, DAR, and DER, affect profitability. CR, DAR, and DER affect profitability by 0.541 or 54.1%, while the remaining 45.9% is influenced by other variables not examined.